Raízes de Fátima : a marketing plan - Hogan, Maria do Carmo Faria Luís Navarro (2020)
The following dissertation has the purpose of developing a marketing plan for Raízes de Fátima. Raízes de Fátima is a start-up and the main service provided is an explanatory tour in Fátima (catholic sanctuary in Portugal). Starting in 2018, Raízes de Fátima is now trying to establish a place in the market as well as find the right target and this dissertation provides the tools for it. With the support of a survey conducted in a Brazilian population that provided the possibility of developing four regression models to better observe the data collected, and secondary data gathered from studies and websites related to the topic at hand, this thesis provides an analysis of the market of religion tourism, examines the competition, and studies the target market of the start-up. At the end of the analysis the main takeaways of the project are: the definition of the main service the start-up should provide, the price to be practiced by the start-up and where to sell the service, among others.